Profil Hematologi Pasien Covid-19 Berdasarkan Beratnya Kasus: Haematology Profile of Covid-19 Patients Based on the Severity of Cases - Taureni Hayati; Mirna Albertina Wijaja; Sri Murtiyani Kusumastuti (Jurnal Sains dan Kesehatan, 2022)
This study aims to determine the hematology profile of Covid-19 patients based on the severity of the case. The method used is descriptive. Data collection techniques are patient clinic data, complete patient blood, NRL, and ALC. The results of the study are a) characteristics of COVID-19 patients in weight that cases in women are more than men, b) the absence of the influence of hemoglobin levels in COVID-19 patients, c) hematocrit values do not affect the incidence of COVID-19, d) there is an effect of leukocytes on the symptoms of COVID-19 patients, e) there is no influence of platelets with the incidence of COVID-19, and f) there is an effect of NLR on the symptoms of COVID-19 patients, and g) there is an effect of ALC on the symptoms of COVID-19 patients. The conclusion of this study is a) there are differences in leukocyte, NLR, and ALC profiles in COVID-19 patients, b) there is no difference in hemoglobin, hematocrit, and platelet profiles in the symptoms of COVID-19 patients, and c) there are significant differences in hematological profiles in COVID-19 patients can help classify COVID-19 patients based on the severity of cases.